2016
DOI: 10.1007/s10802-016-0188-y
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Validity of Teacher and Parent Symptom and Impairment Ratings when Screening for Mental Health Difficulties

Abstract: Although universal screening for mental health difficulties is increasingly recognized as a way to identify children who are at risk and provide early intervention, little research exists to inform decisions about screening, such as the choice of informants and the type of information collected. The present study examined the incremental validity of teacher- and parent-rated (primarily mothers) symptoms and impairment in a non-referred sample of early elementary school children (n = 320, 49 % boys, ages 6 to 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 67 publications
0
7
0
1
Order By: Relevance
“…Findings in the child assessment literature suggest that different informants may confer different facets of psychopathology (De Los Reyes et al, 2015). For instance, whereas self-reported depression may best reflect current emotional distress (Fristad, Weller, Weller, Teare, & Preskorn, 1991;Lewis et al, 2014), observed internalizing symptoms from others (e.g., parents, teachers) may uniquely capture prospective depression risk in youth (Aitken, Martinussen, & Tannock, 2017;Cohen, So, Young, Hankin, & Lee, 2019). This may be why findings across teacher-reported internalizing symptoms and emotion liability/negativity were consistent in the present study, as both measures were indexing risk as opposed to current symptom levels.…”
Section: Discussionmentioning
confidence: 99%
“…Findings in the child assessment literature suggest that different informants may confer different facets of psychopathology (De Los Reyes et al, 2015). For instance, whereas self-reported depression may best reflect current emotional distress (Fristad, Weller, Weller, Teare, & Preskorn, 1991;Lewis et al, 2014), observed internalizing symptoms from others (e.g., parents, teachers) may uniquely capture prospective depression risk in youth (Aitken, Martinussen, & Tannock, 2017;Cohen, So, Young, Hankin, & Lee, 2019). This may be why findings across teacher-reported internalizing symptoms and emotion liability/negativity were consistent in the present study, as both measures were indexing risk as opposed to current symptom levels.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome is the children's pathology according to the [(Caregiver-) Teacher Report Form (C-)TRF, caregiver/teacher version of the Child Behavior Checklist] score between baseline 2 (T2) and post treatment (T3) as well as between T2 and the 6-month follow-up (T4) after end of treatment (37, 38) as the literature shows that mentally ill parents can be biased in rating their children's symptoms (39). Further, teacher ratings have been shown to demonstrate greater predictive validity in the long term ratings (40). In comparison to shorter questionnaires [e.g., Strengths and Difficulties Questionnaire (SDQ) (41)], the CBCL also produces more variance.…”
Section: Methodsmentioning
confidence: 99%
“…Gleichzeitig ging es in der Studie um mögliche Auswirkungen von wahrgenommenen ADHS-Symptomen der Kinder durch die Lehrkräfte, sodass der Einsatz des SDQ angemessen scheint. Der SDQ stellt ein valides und international anerkanntes Instrument dar, bei dem insbesondere das Lehrkrafturteil hohe prognostische Validität besitzt (Aitken, Martinussen & Tannock, 2017…”
Section: Limitationenunclassified